Effectiveness of Training for Peer Counselors to Improve Gender Awareness - Mufida Istati; Helma Nuraini (Bisma The Journal of Counseling, 2022)
The study aimed to discover the effectiveness of training for trainers of peer counselors to improve gender awareness at two Islamic Universities in Banjarmasin City. The study employed a qualitative approach with the true experimental design in the form of a Pre-test Post-test Control Group Design. The study object was gender awareness. Data were collected using the gender awareness scale. The study was conducted in Banjarmasin on students of the Counseling Department of UIN Antasari Banjarmasin and Islamic University of Kalimantan Muhammad Arsyad Al Banjary. The data were analyzed using a T-test. The study discovered that training for trainers of peer counselors is effective to improve gender awareness observed from the significant test difference between the experiment and control groups.